Kinetics and Mechanisms of Extracellular Protein Release by Helicobacter pylori - Schraw, Wayne (American Society for Microbiology, 1999)
To investigate the kinetics and mechanisms of extracellular protein release by Helicobacter pylori, we analyzed the entry of metabolically radiolabeled bacterial proteins into broth culture supernatant. At early time points, vacuolating cytotoxin (VacA) constituted a major extracellular protein. Subsequently, culture supernatants accumulated many proteins that were components of intact bacterial cells. This nonselective release of proteins was associated with a decreasing turbidity of cultures and loss of bacterial viability, indicative of an autolytic process. The rates of VacA secretion and autolysis were each influenced by medium composition, and therefore these may be regulated phenomena. Extracellular release of proteins by H. pylori may be an important adaptation that facilitates the persistence of H. pylori in the human gastric mucus layer. Moreover, entry of proinflammatory proteins into the gastric mucosa may contribute to the induction of a mucosal inflammatory response.